2018
DOI: 10.1182/bloodadvances.2017015230
|View full text |Cite
|
Sign up to set email alerts
|

Natural killer receptor ligand expression on acute myeloid leukemia impacts survival and relapse after chemotherapy

Abstract: Natural killer (NKs) cells provide rapid responses to viral-infected and malignant cells, including acute myeloid leukemia (AML) blasts. The balance among inhibitory and activating signals, delivered by multiple interactions between ligands on target cells and NK receptors, determines the posture of the NK cell response to either one of target cell elimination or tolerance. The aim of this work was to study the influence of the differential expression of activating and inhibitory NK receptor ligands (NKRLs) by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
43
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(47 citation statements)
references
References 39 publications
2
43
1
1
Order By: Relevance
“…DNAM-1 + GM NK-92 cells degranulated against all primary sarcoma explants as well as against the majority of the established cell lines, proving the potential of CD112 and CD155 as tumorspecific markers for targeted immunotherapies (Figures 3, 7). This, along with the absence of the degranulation response of NK cells against healthy donor PBMCs, showed that the use of DNAM-1 + GM NK-92 cells could be restricted/directed only to targets that had elevated CD112 and/or CD155 expression (Figures 2, 7), which is observed in tumors from various origins (65)(66)(67)(68)(69)(70)(71)(72)(73)(74)(75)(76)(77)(78)(79)(80)(81)(82)(83), including osteosarcomas (24).…”
Section: Discussionmentioning
confidence: 99%
“…DNAM-1 + GM NK-92 cells degranulated against all primary sarcoma explants as well as against the majority of the established cell lines, proving the potential of CD112 and CD155 as tumorspecific markers for targeted immunotherapies (Figures 3, 7). This, along with the absence of the degranulation response of NK cells against healthy donor PBMCs, showed that the use of DNAM-1 + GM NK-92 cells could be restricted/directed only to targets that had elevated CD112 and/or CD155 expression (Figures 2, 7), which is observed in tumors from various origins (65)(66)(67)(68)(69)(70)(71)(72)(73)(74)(75)(76)(77)(78)(79)(80)(81)(82)(83), including osteosarcomas (24).…”
Section: Discussionmentioning
confidence: 99%
“…On the basis of clinical data, NK cells appear to play a crucial role in the eradication of acute leukemia [ 26 , 27 , 28 ]. However, the ability of NK cells to mediate a response against tumor cells such as leukemia cells depends on the presence of ligands that are recognized by NK receptors on tumor cells [ 12 , 13 , 26 , 29 ]. In this study, a broad diversity of NK cell responses was observed in vitro against myeloid and lymphoid cell lines.…”
Section: Discussionmentioning
confidence: 99%
“…Cognate ligands are heterogeneously expressed on leukemias. It has been reported that the absence of expression or downregulation of HLA class I molecules, as well as the presence of activating ligands on the surface of leukemia cells, were associated with the reduction of relapse incidence and improved overall survival of patients with leukemia [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, there appears to be large variability in the anti-leukemic effects of 293C3-SDIE, possibly due to differing expression patterns of CD133 between patients. This may also be in part due to evidence of HLA dimorphism and NK cell ligand expression impacting AML therapy (244,245). Furthermore, as described above, autologous patient NK cells may have been functionally impaired, relative to allogeneic NK cells (176).…”
Section: Mabs In Pre-clinical Development-targeting Tumor Antigens Fomentioning
confidence: 99%